(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The success of any institution must be based on means to protect its resources and assets from the waste, loss, misuse and the availability of accurate and reliable data by accounting reports to increase its operational efficiency, namely, that the internal control system is considered as a safety valve for top management in any economic unit. The problem is represented by the need for an efficient system, so to ensure its success, there must exist external parties which monitor and evaluate the performance because of its importance by following clear criteria. So, the research problem came to address performance evaluation indicators which are set by the Federal Board of Supreme Audit (FBSA) and identify the extent of its contribution to achieving an efficient system for the General Commission of Taxes (GCT), fulfil the requirements of the tax reform and identify shortcomings in these indicators, and determine the role of internal control in the GCT to achieve the aspirations of the FBSA to raise the efficiency of tax work performance. The aim of the research stems from the knowledge of the role of the FBSA in evaluating the performance to raise the efficiency of the internal control system and the tax administration in general, as well as find out how to use modern and possible methods and techniques in the control process over tax procedures, and research importance shows the role of the FBSA in evaluating the tax administration performance. The internal control is considered of the fundamental foundations of management’s performance and this is an important and indispensable stage of the tax collection mechanism as a whole, being the cornerstones of the tax system and these could be the cause of achieving the desired economy, and that the use of an efficient system for control with a scientific manner that increases the effectiveness of management’s performance.